Rethinking young people's lives through space and place - Sriskandarajah, Anuppiriya (Sociological studies of children and youth, 2020)
Rethinking Young People's Lives Through Space and Placeexplores three main themes, how children navigate real and imaginary borders, how space constitutes belonging, meaning-making, and representation, and how space informs learning and identities.